Health Education and Early Detection of Anemia in Pregnant Women - Mirawati; Wulandari; Mariati, Nelly (UrbanGreen Central Media, 2021)
Anemia in pregnant women can increase the risk of premature birth, maternal and child mortality, and infectious diseases. In Indonesia, anemia is generally due to iron deficiency. During pregnancy, it is necessary to consume a variety of foods to increase iron in the body. Pregnant women must have good knowledge about nutrition during pregnancy. The purpose of this community service is to increase knowledge of pregnant women and raise awareness of the quality of healthy life so as to prevent anemia in pregnancy. The implementation method is in the form of health education about anemia in pregnancy and early detection of anemia with health checks such as Weight, Blood Pressure and Hemoglobin. The results is to increased the knowledge of pregnant women about anemia and the results of the Hemoglobin examination were obtained from a total of 21 pregnant women, there were a small proportion who had anemia, namely 7 people (33%) and 14 people did not anemia (67%). Early detection of anemia is important for pregnant women because it can prevent complications in pregnancy.